Surgical treatments for women with stress urinary incontinence: the ESTER systematic review and economic evaluation. - Brazzelli, Miriam (Health Technol Assess, 2019)
BACKGROUND: Urinary incontinence in women is a distressing condition that restricts quality of life and results in a large economic burden to both the NHS and women themselves. OBJECTIVE: To evaluate the clinical effectiveness, safety and cost-effectiveness of surgical treatment for stress urinary incontinence (SUI) in women and explore women's preferences. DESIGN: An evidence synthesis, a discrete choice experiment (DCE) and an economic decision model, with a value-of-information (VOI) analysis. Nine surgical interventions were compared. Previous Cochrane reviews for each were identified and updated to include additional studies. Systematic review methods were applied. The outcomes of interest were 'cure' and 'improvement'. Both a pairwise and a network meta-analysis (NMA) were conducted for all available surgical comparisons. A DCE was undertaken to assess the preferences of women for treatment outcomes. An economic model assessed the cost-effectiveness of alternative surgeries and a VOI analysis was undertaken. RESULTS: Data from 175 studies were included in the effectiveness review. The majority of included studies were rated as being at high or unclear risk of bias across all risk-of-bias domains. The NMA, which included 120 studies that reported data on 'cure' or 'improvement', showed that retropubic mid-urethral sling (MUS), transobturator MUS, traditional sling and open colposuspension were more effective than other surgical procedures for both primary outcomes. The results for other interventions were variable. In general, rate of tape and mesh exposure was higher after transobturator MUS than after retropubic MUS or single-incision sling, whereas the rate of tape or mesh erosion/extrusion was similar between transobturator MUS and retropubic MUS. The results of the DCE, in which 789 women completed an anonymous online questionnaire, indicate that women tend to prefer surgical treatments associated with no pain or mild chronic pain and shorter length of hospital stay as well as those treatments that have a smaller risk for urinary symptoms to reoccur after surgery. The cost-effectiveness results suggest that, over a lifetime, retropubic MUS is, on average, the least costly and most effective surgery. However, the high level of uncertainty makes robust estimates difficult to ascertain. The VOI analysis highlighted that further research around the incidence rates of complications would be of most value. LIMITATIONS: Overall, the quality of the clinical evidence was low, with limited data available for the assessment of complications. Furthermore, there is a lack of robust evidence and significant uncertainty around some parameters in the economic modelling. CONCLUSIONS: To our knowledge, this is the most comprehensive assessment of published evidence for the treatment of SUI. There is some evidence that retropubic MUS, transobturator MUS and traditional sling are effective in the short to medium term and that retropubic MUS is cost-effective in the medium to long term. The VOI analysis highlights the value of further research to reduce the uncertainty around the incidence rates of complications. There is a need to obtain robust clinical data in future work, particularly around long-term complication rates. STUDY REGISTRATION: This study is registered as PROSPERO CRD42016049339. FUNDING: The National Institute for Health Research Health Technology Assessment programme.